1999
DOI: 10.1021/ma981937b
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Dynamics in Poly(methylphenylsiloxane) Networks by Dielectric Relaxation Spectroscopy

Abstract: The segmental dynamics of PMPS chains are determined in the bulk liquid and cross-linked networks of varying cross-link density by broad-band dielectric relaxation spectroscopy. A large fragility index [τ(T g*/T) dependence], F 1/2 = 0.77, is found, independent of cross-link density, molecular weight, and T g. Also independent of the above variables is the relaxation shape (characterized by a KWW β parameter of 0.45). Since these parameters quantifying the α process in PMPS networks are insensitive to cross-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 57 publications
2
45
0
1
Order By: Relevance
“…The results of the analysis are included in the figure as well with the solid line being the total fit and the dotted and dashed lines the elastic and quasielastic contributions, respectively. For all curves, the stretching parameter ␤ of the KWW was kept constant at ␤ = 0.4, which is the value that gave the best fit for all wavevectors and is in good agreement with literature values obtained for the segmental relaxation of different polymers with a variety of experimental techniques, 1,[41][42][43][55][56][57] where 0.38Ͻ ␤ Ͻ 0.52 was found. It is clear that the elastic part is very small at this temperature, which shows that there are almost no immobile species in the polymer sample.…”
Section: A Dynamics Of Pmps In the Bulksupporting
confidence: 84%
See 2 more Smart Citations
“…The results of the analysis are included in the figure as well with the solid line being the total fit and the dotted and dashed lines the elastic and quasielastic contributions, respectively. For all curves, the stretching parameter ␤ of the KWW was kept constant at ␤ = 0.4, which is the value that gave the best fit for all wavevectors and is in good agreement with literature values obtained for the segmental relaxation of different polymers with a variety of experimental techniques, 1,[41][42][43][55][56][57] where 0.38Ͻ ␤ Ͻ 0.52 was found. It is clear that the elastic part is very small at this temperature, which shows that there are almost no immobile species in the polymer sample.…”
Section: A Dynamics Of Pmps In the Bulksupporting
confidence: 84%
“…Finally, the relaxation times for the pure segmental relaxation at 300 K are in a relatively good agreement with those of earlier studies on PMPS. 25,32,[40][41][42]59 B. Dynamics of PMPS under severe confinement Figure 2 shows the temperature dependence of the energy resolved elastic scattering intensity for the PMPS25 nanocomposite ͓Fig. 2͑c͔͒ in comparison to those for the PMPS1 homopolymer ͓Fig.…”
Section: A Dynamics Of Pmps In the Bulkmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of network formation on the relaxation behavior of polymer networks is an issue of considerable experimental effort. [5][6][7] Comparison between the dynamic behavior of a covalently entangled and cross-linked polymer, with low volume fraction of cross-links, has shown similar features in both the normal mode and the segmental relaxation regime. 8 However, previous studies have shown a strong influence of cross-link density on the ␣ relaxation characterized by a slowing down of the segmental dynamics as cross-links density, inducing connectivity, increases.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In many studies, the true impact of chemical network density is obscured by several side effects such as morphological heterogeneity and strong physical interaction in segmented polyurethanes, 7 incomplete chemical conversion in acrylates, 6 or anomalous chain flexibility of network strands in polysiloxanes. 5 Some of these side effects can be minimized by controlled preparation of model polymer networks with well-defined molecular architecture. It is known that the appropriate trimerization of isocyanate in the presence of tin compounds produces a regular isocyanourate network.…”
Section: Introductionmentioning
confidence: 99%